Propuesta de renovación hospitalaria y transformación urbana: Un enfoque integral para el mejoramiento del entorno de salud para el hospital Juan Pablo ll del municipio de Aratoca, Santander. (2023)
Large-scale facilities in the Guane region have always been image references in a population, such as churches, town halls, hospitals, etc. Of these great facilities, health centers may be the ones that lack a bit of aesthetics, image, being a little gloomy in their form, rhythm, concept and proposal of finishes and design, classic or common in the region at the time of conception. Our proposal for hospital renovation and urban transformation for the Juan Pablo II hospital in the municipality of Aratoca, Santander, seeks, through the expansion of its services, to improve its image, integration with its immediate environment as a public space, urban planning and green areas, create a new and better image of this great facility that welcomes you to the urban center of the municipality, but at the same time we also want to expose its history, culture and economy through an urban strip that links from the access to the municipality with urban articulating nodes until the end of the urban area of the municipal seat;